2020
DOI: 10.1111/apa.15341
|View full text |Cite
|
Sign up to set email alerts
|

Pain is frequent in children with cerebral palsy and negatively affects physical activity and participation

Abstract: Cerebral palsy (CP) is the most common motor functional disability in childhood 1,2. Studies have reported that pain is one of the most frequent problems among children with CP, and lack of acknowledgement as well as a lack of acting on the pain negatively affects their quality of life 3-6. In regard to this, pain will, as the limiting factor for children with CP, affect their quality of life by being incapable or unable to participate in physical leisure activities such as soccer, swimming, gymnastics and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 26 publications
1
22
1
1
Order By: Relevance
“…However, a limitation of the CPOP registry that we used is that it was not designed to measure pain and that means that pain was not measured, and reported, using a validated tool. 10 Pain was reported as only yes or no by the child or the parents, and there was no grading of the severity of the pain. This limitation may explain why the association between hip contracture and pain was not statistically significant in this study, contrary to the results by Schmidt et al 1 Our study indicated that there seemed to be regional differences in the incidence of hip contractures over time and there may be a number of reasons for this.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a limitation of the CPOP registry that we used is that it was not designed to measure pain and that means that pain was not measured, and reported, using a validated tool. 10 Pain was reported as only yes or no by the child or the parents, and there was no grading of the severity of the pain. This limitation may explain why the association between hip contracture and pain was not statistically significant in this study, contrary to the results by Schmidt et al 1 Our study indicated that there seemed to be regional differences in the incidence of hip contractures over time and there may be a number of reasons for this.…”
Section: Discussionmentioning
confidence: 99%
“…This was in contrast with our results, as we did not show a significant association between hip contractures and pain in the lower extremities. However, a limitation of the CPOP registry that we used is that it was not designed to measure pain and that means that pain was not measured, and reported, using a validated tool 10 . Pain was reported as only yes or no by the child or the parents, and there was no grading of the severity of the pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 50% of children with CP suffer pain from moderate to severe intensity and at multiple body locations [ 1 , 2 ]. Pain negatively affects quality of life [ 2 , 3 ] and participation [ 2 , 4 ]. Furthermore, individuals with CP have altered somatosensory processing and pain sensitivity [ 5 ], requiring the development of specific coping strategies to manage pain [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of research on pain in CP 1,2 and population‐based studies report the most generalizable estimations of pain prevalence 1 . To date, there are seven population‐based studies representative of the wider CP population 3–9 …”
mentioning
confidence: 99%